Estimation of the Student Employment in the Aviation Industry Based on Novel Fractional Error Accumulation Grey Model - Yali Zhang; Xiaojiang Yang; Wei Cui (Journal of Mathematics)
To improve the employment forecasting accuracy of traditional grey models, the grey model with the fractional error accumulation is proposed. The estimation error is accumulated. The proposed model can make use of the initial value x1 and can give more attention to the error of new data. The monotonicity of the simulative value by the proposed model is data-driven and uncertain. The comparison results show that the proposed model can enhance the forecasting accuracy of traditional grey model. It deserves to be applied to employment forecasting.